Penyuluhan Pentingnya Penggunaan Helm Standar Guna Menurunkan Angka Kejadian Cedera Otak Di SMAN 1 Pringgabaya - Muhammad Rosyidi, Rohadi; Priyanto, Bambang; Januarman, Januarman; Alaydrus, Mukaddam; Zulkarnaen, Decky Aditya (Universitas Mataram, 2024)
Brain injuries have the third largest prevalence of other injuries in Indonesia. Most brain injuries occur on the road because of motorbike accidents. The only effective way to reduce the number of deaths due to brain injuries that occur in motorbike accidents is to use a helmet. SMA 1 Pringgabaya was chosen because the area is densely populated and awareness of wearing helmets is still low. Activities are carried out using lecture methods, demonstrations and carrying out pre-tests and post-tests. The activity was held in the SMA 1 Pringgabaya Hall on May 4, 2024, with 200 students participating in the training. The students' post-test results were 83.3, including knowledge in the good category. There is an increase in the knowledge of service participants regarding the advice of using helmets and preventing brain injuries.